Negotiation in Collaborative Working Environment for the Next Generation of Product Design - Coutinho, C.; Cretan, A.; Agostinho, C.; Jardim-Goncalves, R. (Proceedings of the ASME 2015 International Mechanical Engineering Congress & Exposition (ASME IMECE 2015), 2015)
Negotiation in collaborative manufacturing environments drive new ways to perform interoperability between industrial companies. The networks of SMEs are a novel segment in a highly competitive area, supported by numerous partners and applications which need to collaborate and to be interoperable. Particularly, the subcontracted small and medium enterprises (SMEs) need to be flexible towards the changes that are imposed by the major contractors, doing so at the lowest cost. This paper proposes a framework which advocates negotiations as a pillar mechanism to support innovation during the development of services in industrial collaborative working environments, and reflects the results of the European research project H2020 C2NET.